THE FEATURES OF A NOVICE TEACHER TALK IN CLASSROOM INTERACTION: AN ANALYSIS USING SETT FRAMEWORK - Risna Saswati; Soraya Soraya (PROJECT (Professional Journal of English Education), 2023)
This study sheds light on the features of the SETT framework employed by a novice teacher in order to facilitate learning opportunities. The method applied is descriptive qualitative methods using classroom observation, classroom recording, and field notes as data collection techniques. The SETT framework is chosen to find out the dominant features employed by a novice teacher while interacting with learners in the classroom. The results are all modes in the SETT framework applied by the novice teacher with the IRF interactional pattern as the dominant interaction pattern in classroom interaction. Additionally, the type of display questions is found out in interaction in which it is used to elicit the learners’ responses. The result of this study is the SETT framework is not applicable to be used to evaluate novice teachers since the dominant activities in the classroom are not to reach communicative activities due to his/her teaching experiences. However, the deviant modes are found: shifting and divergent modes. The divergent modes found in this study do not facilitate learning opportunities for learners to have communicative interaction.